ANALISA PENGARUH KUALITAS HUBUNGAN DAN LOYALITAS PELANGGAN DENGAN ETIKA PERILAKU PENJUALAN DI INDUSTRY KEUANGAN DI PEKANBARU (STUDI KASUS PADA SECTOR LEASING/PEMBIAYAAN MOBIL) - riki hanri malau (JURNAL AL-IQTISHAD, 2015)
Today the awareness of the ethical behavior getting higher in competitive pressures, the implications of ethical conduct for leasing institutions have become an important determinant of customer loyalty. The aim of this study was to develop a conceptual framework to investigate the relationship between sales of ethical behavior, relationship quality and customer loyalty. The proposed model is tested on data collected from 70 people salesman from various leasing in Pekanbaru. Structural equation modeling techniques are employed using SPSS V.17 to verify the reliability and validity of the scale and to test the effect of. Results showed that positive ethical behavior is influenced by the quality of relationships and costumer loyalty on sales operation. The findings also show that customer confidence in leasing has a positive effect on leasing customer commitment. Results of this study the position of customer trust and customer commitment as the main mechanism through which the beneficial effects of the ethical behavior of sales is realized. However, research shows that the perception of ethical behavior has a huge impact on the development and maintenance of customer relationships with leasing institutions. For the leasing manager, who appreciate the importance of long-term relationships with their customers, should minimize unethical sales behavior to reaches the environment of intense competition.